The effect of total standing duration during sit-stand regimes on cognitive performance, rating of perceived exertion and heart rate frequency - Berndt, Ethan (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2017)
Although there may be numerous health benefits of sit-stand workstations, the effects of sedentary or non-sedentary work configurations on cognitive performance and executive function remain unclear (Bantoft et al., 2016). It is essential to determine any performance effects of these different work configurations; as improvements in the workplace, working posture and discomfort need to be justified in terms of improvements (or no deterioration) in work performance (Liao and Drury, 2000). The aim of the current research was to investigate the effect of two sit-stand regimes differing in total standing duration, on cognitive task performance, physiological responses and subjective ratings of perceived exertion. This laboratory based investigation incorporated a repeated measures design, where a test battery was utilized. Three experimental conditions were tested during three separate testing sessions by 30 participants. Condition 2 (15 minutes standing, followed by 45 minutes seated) and Condition 3 (15 minutes seated, followed by 15 minutes standing, followed by 15 minutes seated, followed by 15 minutes standing) were compared to each other and Condition 1 (60 minutes seated). The findings of this study show that even though the two different sit-stand regimes did not result in a significant impact on cognitive task performance, an immediate postural effect for psychomotor response time and a delayed postural effect for working memory were found. The participants perceived Condition 3 as the most physically exerting condition. Heart rate frequency was not significantly different between the conditions, but the immediate seated posture had a significantly lower heart rate frequency compared to the standing posture; indicating that being seated elicited lower energy expenditure compared to standing. Heart rate frequency while standing had a greater degree of variation compared to being seated. Taking the findings of this study into account, it is recommended that: one should be seated while performing this type of working memory task; that one should be standing while performing this type of psychomotor task; that the recommendation that implementing standing at work can be used as a blanket strategy to increase energy expenditure in all individuals needs to be explored further and that individual differences may impact energy expenditure.
Keywords: Standing position; Sedentary behavior; Work environment; Employee health promotion; Office furniture -- Design; Industrial hygiene; Employees -- Health risk assessment; Human engineering